Assessment of serum BDNF levels in complex rehabilitation of patients with ischemic stroke using traditional approaches to the restoration of motor functions - S. D. Kazakov; E. S. Koroleva; N. G. Brazovskaya; A. A. Zaytsev; S. A. Ivanova; V. M. Alifirova (Бюллетень сибирской медицины)
Aim. To assess the relationship between changes in serum brain-derived neurotrophic factor (BDNF) level, regression of motor deficiency, and restoration of functional activity in patients with ischemic stroke after stage II of medical rehabilitation.Materials and methods. The study included 49 patients with ischemic stroke in the middle cerebral artery after stage I of medical rehabilitation. Group I (n = 32) went through stage II of rehabilitation in the early recovery period, group II (n = 17) was discharged for outpatient monitoring at the place of residence. Observation points: day 14 and day 90. Evaluation scales: National Institute of Health Stroke Scale (NIHSS), Fugle – Meyer Scale (FMA), Modified Rankin Scale (mRS). Serum BDNF levels were determined using a MAGPIX multiplex analyzer (Luminex, USA).Results. A comparative analysis of the studied population showed that patients who underwent motor rehabilitation in the early recovery period had greater regression of neurologic deficit according to the ΔNIHSS scale (pgr.I–II = 0.043), a more pronounced increase in the functional activity on the ΔmRS scale (pgr.I–II = 0.047), and positive dynamics according to the FMA scale (pday14–90 = 0.003) in comparison with patients who received outpatient follow-up. The concentration of BDNF was significantly reduced by the end of the early recovery in the group II (pday14–90_gr.II = 0.002). On the contrary, there was no decrease in the level of the BDNF (pday14–90_gr.I = 0.613) in the group of patients undergoing rehabilitation.Conclusion. The results of the study demonstrated the clinical effectiveness of stage II of the comprehensive rehabilitation of patients in the early period of stroke recovery. We can suggest that the success of neurorehabilitation is closely associated with an increase of the BDNF level against the background of its performance. This makes BDNF a potential marker of evaluating the effectiveness of ongoing rehabilitation treatment.